2005
DOI: 10.1021/jf050076k
|View full text |Cite
|
Sign up to set email alerts
|

Migration Studies To Assess the Safety in Use of a New Antioxidant Active Packaging

Abstract: Both specific and overall migration tests have been applied to new experimental food packaging-active plastic films with antioxidant properties, including in its composition a natural rosemary extract. Determination of volatile and semivolatile compounds migrating from plastic to the four established simulants showed that both specific and overall migration was very low. The results obtained gave values 20 times lower than the established limits in the worst case. So, from the point of view of health risk, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 29 publications
1
38
0
2
Order By: Relevance
“…An antioxidant active packaging film is prepared by introducing antioxidants into the food packaging material, instead of adding them directly to the food, to delay the auto-oxidation of the food products (14). A wide range of biocompounds, most of which are synthetic molecules, have been used as antioxidant agents incorporated into food packaging materials (15).…”
Section: Introductionmentioning
confidence: 99%
“…An antioxidant active packaging film is prepared by introducing antioxidants into the food packaging material, instead of adding them directly to the food, to delay the auto-oxidation of the food products (14). A wide range of biocompounds, most of which are synthetic molecules, have been used as antioxidant agents incorporated into food packaging materials (15).…”
Section: Introductionmentioning
confidence: 99%
“…An innovative approach with enhanced shelf life of foodstuffs while improving their quality, safety and integrity, consists of active packagings (Dawson, 2002;Nerín et al, 2006;Suppakul, Miltz, Sonneveld, & Bigger, 2003a;Tovar, Salafranca, Sánchez, & Nerín, 2005;Vermeiren, Devlieghere, van Beest, de Kruijf, & Debevere, 1999), whose extra functions are obtained by incorporating actively functional ingredients or materials into packaging systems (Han, 2002). These components are usually applied as sachets inserted into the package or as adhesive-bonded label to the inner wall of the package, in the closure or in the packaging material through dissolution or dispersion into the plastic material, or by immobilization of oxidizing enzymes in the packaging material (De Kruijf et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Garces et al patented an antioxidant coating composed of a polymer blend that contains plant extracts that scavenge free radicals [91]. Tovar et al demonstrated that this antioxidant coating may be classified as non-migratory as it demonstrated migration that was 20 times less than the legal limits for the European Union [92]. Furthermore, this antioxidant active packaging coating derives activity from free radical scavenging in the packaging headspace, thus not requiring direct contact with the food [93][94][95].…”
Section: Antioxidantmentioning
confidence: 99%